Quality assessment and storage stability of developed lactose hydrolyzed yoghurt using β-galactosidase - Hardwari Lal; Sharanagouda B; Sumit Mahajan; Shiv; Indu Panchal (Indian Journal of Dairy Science, 2026)
The present study aimed to develop lactose hydrolyzed yoghurt by using different concentrations of lactase enzyme in a yoghurt mix to produce acceptable quality lactose hydrolyzed yoghurt with the incorporation of stabilizer and emulsifier. Physico-chemical, rheological, microbiological, and sensory characteristics of the products were studied. It was observed that the penetration value, whey syneresis, and acidity of the lactose-hydrolyzed yoghurt (LHY) increased with the increased level of lactose hydrolysis. Whereas, setting time and sensory attributes were decreased correspondingly with the increased degree of lactose hydrolysis. The viscosity of control and all other treatments were decreased with increased temperature at a constant shear rate. Based on the sensory evaluation 0.6ml/L lactase enzyme was adjudged as very much comparable to control. Hence, 0.6 ml/L was selected for further studies. The developed products of lactose hydrolyzed yoghurt were stored at 4±1℃ and evaluated at 7 days intervals for 28 days. There was a decrease in pH and an increase in acidity throughout the storage period at refrigeration temperature. The standard plate count and starter count increased up to the 14th day but after that SPC and starter count decreased with the progression of the storage period. The yeast and mold count increased with the progression of the storage period. Coliforms were absent in all the samples.